The Seven Deadly Sins: Anthony Hecht’s Emblem Poems - Valli, Elena (Eikón / Imago, 2023)
Many poets writing after World War II felt a sense of diffidence towards the great ideals of history and religion. They offer a satiric interpretation of their time, and their work often perverts the typological reading of history illustrated in the Bible by opposing the promises of a second coming by Christ with the horrors of the war and the Holocaust, suggesting that the concept of “sacrifice” has no redemptive value. Anthony Hecht, an American post-war formalist, expresses this message through an ekphrastic medium, specifically emblems, inspired by mediaeval culture and Renaissance poetry. One of his early works, The Seven Deadly Sins, in collaboration with the engraver Leonard Baskin, presents a modern collection of emblem poems featuring the figure of Christ, which like the emblematic form can be seen as “word made flesh”. Through their combinations of icons and words, the emblems become the perfect form to assess the dialectical opposition between God and man, body and soul, past and present.